2020
DOI: 10.1177/0733464819898667
|View full text |Cite
|
Sign up to set email alerts
|

The Well-Being of Carers of Older Aboriginal People Living in the Kimberley Region of Remote Western Australia: Empowerment, Depression, and Carer Burden

Abstract: Objective: To describe demographic features and well-being of carers of Aboriginal Australians aged ≥45 years in remote Western Australia. Method: Carer burden, empowerment, and depression were assessed in 124 Aboriginal carers in four remote Aboriginal communities. Results: Carers were aged 38.8 ± 15.0 years, 73.4% were female, and 75.8% were children or grandchildren of the person cared for. The mean Zarit-6 score was 3.7 ± 3.6. Attending high school (odds ratio [OR] = 0.3; 95% confidence interval [CI] = [0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…The various methods of assessing content validity reported in six of the studies included brief descriptions of content revision [ 31 , 45 ], calculation of the content validity ratio and content validity index [ 32 ], rating of measurement tool scale items by expert panels [ 20 , 43 ], and independent item ratings and participants readability and clarity [ 44 ]. The face validity of measurement tools, for example, difficulty and relevance of response items, was assessed with a participant feedback approach in only two studies [ 20 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The various methods of assessing content validity reported in six of the studies included brief descriptions of content revision [ 31 , 45 ], calculation of the content validity ratio and content validity index [ 32 ], rating of measurement tool scale items by expert panels [ 20 , 43 ], and independent item ratings and participants readability and clarity [ 44 ]. The face validity of measurement tools, for example, difficulty and relevance of response items, was assessed with a participant feedback approach in only two studies [ 20 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 26 studies reviewed, seven reported one or more aspects of measurement tool feasibility and/or clinical utility in terms of who carried out the assessment [ 15 , 45 ], the number of missing responses [ 17 , 20 , 48 ], participants self-reported experiences of using the tool [ 20 , 39 , 43 , 48 ], as well as the amount of time needed to complete an assessment [ 20 , 39 , 43 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although most people with functional limitations were receiving support, this was predominantly provided by family members and friends, with potential implications for carers' health and well-being. 24,25 Our data were collected prior to the advent of Australia's National Disability Insurance Scheme (NDIS) and My Aged Care, which Islander people access aged care at lower than expected rates given their high level of need, and that access to culturally safe services is limited. 26 Aboriginal and Torres Strait Islander people living in remote areas have significantly reduced access to services.…”
Section: Discussionmentioning
confidence: 99%
“…Although most people with functional limitations were receiving support, this was predominantly provided by family members and friends, with potential implications for carers' health and well‐being 24,25 . Our data were collected prior to the advent of Australia's National Disability Insurance Scheme (NDIS) and My Aged Care, which provide funding to individuals with disability to access support and services.…”
Section: Discussionmentioning
confidence: 99%